The efficacy of intravitreal dexamethasone implant for branch retinal vein occlusion related macular edema - Pandey, Latika; Phogat, Jitender; Dahiya, Monika; Verma, Ritesh; P., Arjun; Dhull, V. K. (International Journal Of Community Medicine And Public Health, 2022)
Background: To study the efficacy of intravitreal injection of dexamethasone implant on central macular thickness in patients with BRVO. Methods: A prospective, longitudinal and interventional study was conducted on 30 patients of BRVO presenting to our OPD over a period of one year. Thorough history and detailed ocular examination was done. All cases included in this study received intravitreal injection of dexamethasone implant and were followed up at the first, third and sixth month post-injection to record any change in BCVA, CMT and IOP. Results: In this study, the mean age of patients was 60.67±7.02 years with a M:F ratio of 1:2. Maximum patients (46.6%) were of 61-70 years age group. A significant change from baseline was observed in BCVA and CMT at 1, 3 and 6 months post injection. BCVA significantly improved at 6th month (0.46±0.20 log MAR) compared to the mean BCVA at 3rd month (0.39±0.15 log MAR) (p<0.001). At the 6th month follow up, the mean CMT (338.33±77.91 µm) (p<0.001) was significantly lower compared to the baseline value (536.23±114.56 µm) (p<0.001) but got significantly increased compared to the mean CMT at third month (p<0.001). IOP values were significantly higher at 1 month (p<0.001) and 3 months (p<0.001) compared to the baseline value. Conclusions: Dexamethasone implant 0.7 mg is beneficial in the improvement of BCVA and treatment of macular edema due to BRVO. However, any beneficial effect on visual acuity and macular edema on OCT seen initially, starts weaning off after 3 months.